Health risk assessment of exposure to polycyclic aromatic hydrocarbons in household indoor environments - Tames, María Florencia (2021)
Airborne particles are able to transport the potentially mutagenic and carcinogenic compounds adsorbed to their surfaces, such as polycyclic aromatic hydrocarbons (PAHs). As a result, they can affect human health and, consequently, the quality of life. In the present paper, we analyzed household airborne particles and estimated the human health risk due to PAH inhalation. Households from Cordoba city (Argentina) were selected for collecting weekly samples of total suspended particles, fine particles (> 2.5 µm) and submicron particles (< 1 µm) during a one-month period in both winter and summer. We found differences in the PAH composition among the three particle sizes, with the PAH levels being particularly high during summer for all three fractions, probably due to pollutants coming from outside or the persistence of pollutants inside homes. In addition, urban households had higher PAH levels than suburban houses. However, the calculated health risks due to the inhalation of particles never exceeded the levels recommended by the Environmental Protection Agency of the United States (< 1 in 10,000) for any age group. Our results, despite the relatively small number of houses included in the study, provide an indication of the likely exposure range of the population in urban environments of developing countries.